2010
DOI: 10.1521/jscp.2010.29.7.727
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits from Training in Self-Compassionate Self-Regulation? A Study of Smoking Reduction

Abstract: Self-compassion has been found to promote well-being but research has yet to examine whether training in self-compassion improves self-regulation (Gilbert, 2005(Gilbert, , 2009Neff, 2003). the present study sought to examine the impact and moderators of a self-compassion intervention on the self-regulation of cigarette smoking. one hundred and twenty-six smokers seeking to quit were randomly assigned to one of four interventions, of which one involved engaging in selfcompassionate imagery and self-talk at ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 38 publications
7
131
0
4
Order By: Relevance
“…Results replicate the findings of Sirois et al (2015a) and other studies which found self-compassion to be associated with healthier behaviours in general population samples (e.g. Kelly et al, 2010;Schoenefeld and Webb, 2013).…”
Section: Mediation Modelsupporting
confidence: 87%
“…Results replicate the findings of Sirois et al (2015a) and other studies which found self-compassion to be associated with healthier behaviours in general population samples (e.g. Kelly et al, 2010;Schoenefeld and Webb, 2013).…”
Section: Mediation Modelsupporting
confidence: 87%
“…In a 2009 study, Kelly and colleagues found that a self-compassion intervention for chronic acne sufferers, in which participants were trained to reduce self-attacks, significantly decreased symptoms of depression, skin complaints, and feelings of shame compared to the control group. In a subsequent study, Kelly, Zuroff, Foa, and Gilbert (2010) found that a self-compassion imagery and self-talk intervention on a group of smokers looking to quit reduced daily smoking more rapidly than a baseline self-monitoring condition. There is also evidence supporting Gilbert's Compassionate Mind Training (CMT; Gilbert & Irons, 2005) among clinical populations, demonstrating that CMT may be an effective treatment for lessening feels of shame and self-criticism that often play a prominent role in the manifestation of disorders such as major depression (Gilbert & Proctor, 2006;Mayhew & Gilbert, 2008).…”
Section: Future Directions and Limitationsmentioning
confidence: 93%
“…As the only study to examine the efficacy of a self-compassion based intervention with a substance use disorder, Kelly, Zuroff, Foa & Gilbert (2010), stands out as an exemplar of a solid treatment comparison study. The authors point out that the study was short-term, and that it focused on reducing use instead of quitting, and that the participants were light smokers, which means that the findings may not apply to heavy smokers.…”
Section: Self-compassion Researchmentioning
confidence: 99%